Phase 1/1b Studies of UCB0599, an Oral Inhibitor of α‐Synuclein Misfolding, Including a Randomized Study in Parkinson's Disease. Issue 10 (12th August 2022) - Smit, Johan Willem; Basile, Peter; Prato, Maria Key; Detalle, Laurent; Mathy, François‐Xavier; Schmidt, Astrid; Lalla, Marianna; Germani, Massimiliano; Domange, Coralie; Biere, Anja‐Leona; Bani, Massimo; Carson, Stan; et al.
Abstract: Background: Parkinson's disease (PD) and its progression are thought to be caused and driven by misfolding of α‐synuclein (ASYN). UCB0599 is an oral, small‐molecule inhibitor of ASYN misfolding, aimed at slowing disease progression. Objective: The aim was to investigate safety/tolerability and pharmacokinetics (PK) of single and multiple doses of UCB0599. Methods: Safety/tolerability and PK of single and multiple doses of UCB0599 and its metabolites were investigated in two phase 1 studies in healthy participants (HPs), where food effect and possible interaction with itraconazole (ITZ) were assessed (UP0030 [randomized, placebo‐controlled, dose‐escalation, crossover study, N = 65] and UP0078 [open‐label study, N = 22]). Safety/tolerability and multi‐dose PK of UCB0599 were subsequently investigated in a phase 1b randomized, double‐blind, placebo‐controlled study of participants with PD (UP0077 [NCT04875962], N = 31). Results: Across all studies, UCB0599 displayed rapid absorption with linear, time‐independent PK properties; PK of multiple doses of UCB0599 were predictable from single‐dose exposures. No notable food‐effect was observed; co‐administration with ITZ affected UCB0599 disposition (maximum plasma concentration and area under the curve increased 1.3‐ and 2 to 3‐fold, respectively) however, this did not impact the safety profile. Hypersensitivity reactions were reported in UP0030 (n = 2) and UP0077 (n = 2). Treatment‐related adverse events occurred in 43% (UCB0599), and 30% (placebo) of participants with PD were predominantly mild‐to‐moderate in intensity and were not dose related. Conclusions: Seventy‐three HPs and 21 participants with PD received UCB0599 doses; an acceptable safety/tolerability profile and predictable PK support continued development of UCB0599 for the slowing of PD progression. A phase 2 study in early‐stage PD is underway (NCT04658186). © 2022 UCB Pharma. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. Abstract : UCB0599, an oral small‐molecule inhibitor of alpha‐synuclein misfolding, aims to slow Parkinson's disease (PD) progression. During Phase 1/1b studies, UCB0599 demonstrated an acceptable safety/tolerability profile and predictable pharmacokinetics in healthy participants, including older individuals, and participants with PD. These data have informed the further clinical development of UCB0599.